Effect of triptolide and chemotherapy on carcinoembryonic and carbohydrate antigens levels and first-line treatment of recurrent nasopharyngeal carcinoma - Liu, Cui; Yuan, Xiaolin; Liu, Xiaobo; Liang, Kuai; Ni, Zhigang; Yu, Gaoxin; Zhu, Li (Cellular and Molecular Biology, 2021)
To investigate the first-line treatment of recurrent Nasopharyngeal Carcinoma treprimcab combined with chemotherapy. From January 2019 to January 2020, 48 patients with recurrent nasopharyngeal Carcinoma (RNPC) were treated in our hospital. According to the method of the random number, 24 patients were divided into the combined group and the Control Group. The patients in the combined group were given the Combined Treatment of triptolide and chemotherapy. While the Control Group only received chemotherapy. The therapeutic effects and adverse reactions of the two groups were compared, the levels of Carcinoembryonic Antigen (CEA) and carbohydrate Antigen 19-9 (CA19-9) were measured before and after treatment. The total effective rate of the combined group was 79.17% higher than that of the control group (62.50%). The total effective rate of the two groups was statistically significant (P & Lt; 0.05). The incidence of grade i/ii adverse reaction in the control group was lower than that in the combined group, such as nausea and vomiting, oral mucositis, Leukopenia, liver and kidney function damage, central granulocyte count reduction, anaemia adverse reaction. The incidence of grade iii/iv Adr in the control group was higher than that in the combined group. The incidence of grade i/ii Adr in the thrombocytopenia group was higher than that in the combined group, and the incidence of grade iii/iv Adr in the control group was lower than that in the combined group. The side effects of nausea and vomiting and oral mucositis in the control group and the combined group were statistically significant (P & Lt; 0.05). There was no significant difference between the control group and the combined group in the incidence of Leukopenia, liver and kidney injury, neutrophil, anaemia and Thrombocytopenia (P & GT; 0.05). The level of CD4 + / CD8 + in control group and combined group before treatment was higher than that after treatment (P & Lt; 0.05). The quality of life of the combined group was 91.67% higher than that of the control group (70.83%). The quality of life of the control group was significantly higher than that of the combined group (P & Lt; 0.05). The levels of CEA and CA19-9 in the two groups after treatment were lower than those before treatment, and the levels of CEA and CA19-9 in the combined group were lower than those in the control group (P & Lt; 0.05). The first-line treatment of recurrent nasopharyngeal Carcinoma with triprimmab combined with chemotherapy has a good clinical effect and has a broad clinical research prospect.